The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1021/ja9035169
|View full text |Cite
|
Sign up to set email alerts
|

High Oxidation State Rhodium and Iridium Bis(silyl)dihydride Complexes Supported by a Chelating Pyridyl-Pyrrolide Ligand

Abstract: New rhodium and iridium complexes containing the bidentate ligand 3,5-diphenyl-2-(2-pyridyl)pyrrolide (PyPyr) were prepared. The bis(ethylene) complex (PyPyr)Rh(C(2)H(4))(2) (3) reacted with HSiEt(3), HSiPh(3), and HSi(t)BuPh(2) to produce the 16-electron Rh(V) bis(silyl)dihydrides (PyPyr)Rh(H)(2)(SiEt(3))(2) (8), (PyPyr)Rh(H)(2)(SiPh(3))(2) (9), and (PyPyr)Rh(H)(2)(Si(t)BuPh(2))(2) (10), respectively. The analogous Ir(V) bis(silyl)dihyride (PyPyr)Ir(H)(2)(SiPh(3))(2) (11) has also been synthesized. X-ray crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
43
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 70 publications
8
43
0
1
Order By: Relevance
“…They revealed that the isomer of [Rh{κ 2 -(N,N)-(C 6 F 5 )NC(Me)CHC(Me)N(C 6 F 5 )}(H)-(SiMe 3 )(CO)] (10a), which exhibits a mutual cis orientation of the hydrido and the carbonyl ligands and in which the silyl ligand occupies the apical position in a square-pyramidal complex, is the only isomer that converged to a stable structure (Figure 8; see the Supporting Information). Such a geometry with the silyl ligand in the apical position can also be found for [Rh{κ 2 -(N,N)-3,5-diphenyl-2-(2-pyridyl)-pyrrolido}(H)(SiPh 3 )(PPh 3 )] [35] and trans-[Os(SiR 3 )(Cl)-(CO)(PPh 3 ) 2 ]…”
Section: Thementioning
confidence: 54%
See 2 more Smart Citations
“…They revealed that the isomer of [Rh{κ 2 -(N,N)-(C 6 F 5 )NC(Me)CHC(Me)N(C 6 F 5 )}(H)-(SiMe 3 )(CO)] (10a), which exhibits a mutual cis orientation of the hydrido and the carbonyl ligands and in which the silyl ligand occupies the apical position in a square-pyramidal complex, is the only isomer that converged to a stable structure (Figure 8; see the Supporting Information). Such a geometry with the silyl ligand in the apical position can also be found for [Rh{κ 2 -(N,N)-3,5-diphenyl-2-(2-pyridyl)-pyrrolido}(H)(SiPh 3 )(PPh 3 )] [35] and trans-[Os(SiR 3 )(Cl)-(CO)(PPh 3 ) 2 ]…”
Section: Thementioning
confidence: 54%
“…[11,31] The NMR spectroscopic data are in accordance with those found for other bis(silyl)-rhodium(V) complexes, in which the silyl ligands are in a mutual trans orientation. [35] DFT calculations were performed to model conceivable configurations of 10a and 16. They revealed that the isomer of [Rh{κ 2 -(N,N)-(C 6 F 5 )NC(Me)CHC(Me)N(C 6 F 5 )}(H)-(SiMe 3 )(CO)] (10a), which exhibits a mutual cis orientation of the hydrido and the carbonyl ligands and in which the silyl ligand occupies the apical position in a square-pyramidal complex, is the only isomer that converged to a stable structure (Figure 8; see the Supporting Information).…”
Section: Thementioning
confidence: 99%
See 1 more Smart Citation
“…The cycle A is completed by addition of HSi(OEt) 3 to 10 , which shows the elimination of 4 a (i.e., 11 is formed) and MeSSi(OEt) 3 . This process presumably occurs either by sigma‐bond metathesis through an η 2 ‐silane,22 for example, F , or oxidative addition to give a Rh V species 23. Intermediates, such as F , have recently been invoked in reactivity of CS bonds with silanes 13a.…”
Section: Resultsmentioning
confidence: 99%
“…13,14 Although there are only a few metal complexes of pyridylpyrrolide in literature, it has been shown that this ligand can stabilize high-valent, polyhydride iridium complexes. [15][16][17][18][19][20][21][22][23] The pyridylpyrrolide derivative that will be implemented in this work is the ligand 3,5-bis(trifluoromethyl)-2-(2′-pyridyl)pyrrole [(X)(L)] (X = H + or K + ). 14 The choice of the electron withdrawing trifluoromethyl groups originates from the idea of diminishing the basicity of the pyrrolide amine, thus lessening the chance of L − experiencing protonation and subsequent demetallation in the presence of acid or adventitious H + sources.…”
mentioning
confidence: 99%